Big Data and Ideational Institutionalism. Reconsidering the Possibilities and Limitations of Google Ngram in the Study of Ideas - Thomas Kestler (Politische Vierteljahresschrift, 2024)
Abstract Ideas and ideational change are difficult to grasp. When exactly did the idea of sustainability emerge? How has the meaning of democracy changed over time? Did ideational change precede or follow institutional change? These and many similar questions are highly relevant to the emerging field of ideational institutionalism, but they are difficult to answer conclusively without reliable data. Google Books Ngram Viewer , a~tool introduced in 2011, opens up new possibilities in this regard by allowing the analysis of millions of print sources over time. However, after initial euphoria, its use has waned somewhat due to growing doubts about its reliability and the validity of the results it produces. Some of these problems have been addressed, but the debate about the potential and limitations of Google Books Ngram Viewer is ongoing. This research note will contribute to this debate by proposing a~systematization for the use of search terms based on the concept of belief systems and by presenting the results of a~reliability test for the German language corpus. - @Ideen und ideeller Wandel sind nur schwer zu erfassen. Wann genau ist die Idee der Nachhaltigkeit entstanden? Wie hat sich die Bedeutung des Demokratiebegriffs im Laufe der Zeit verändert? Ging der ideelle Wandel dem institutionellen Wandel voraus oder folgte er ihm? Diese und viele ähnliche Fragen sind im aufstrebenden Bereich des ideellen Institutionalismus von großer Bedeutung, lassen sich aber ohne verlässliche Daten nur schwer schlüssig beantworten. Das 2011 eingeführte Tool Google Books Ngram Viewer eröffnet in dieser Hinsicht neue Möglichkeiten, da es die Analyse von Millionen von gedruckten Quellen im Zeitverlauf ermöglicht. Nach anfänglicher Euphorie ist die Nutzung dieses Tools jedoch etwas abgeflaut, da zunehmend Zweifel an seiner Reliabilität und der Validität der Ergebnisse aufkamen. Einige der Probleme sind inzwischen behoben worden, aber die Debatte über die Möglichkeiten und Grenzen von Google Books Ngram Viewer ist noch nicht abgeschlossen. Der vorliegende Forschungsbericht leistet einen Beitrag zu dieser Debatte, indem er eine Systematisierung basierend auf dem Konzept der belief systems für die Verwendung von Suchbegriffen vorschlägt und die Ergebnisse eines Reliabilitätstests für den deutschsprachigen Korpus vorstellt.
Keywords: 330; Ideational institutionalism; Corpus linguistics; Belief systems; Google Ngram; Big data; Ideenbasierter Institutionalismus; Korpuslinguistik